How to execute Context, Input, Process, and Product evaluation model in medical health education - So young Lee; Jwa-Seop Shin; Seung-Hee Lee (Journal of Educational Evaluation for Health Professions, 2019)
Improvements to education are necessary in order to keep up with the education requirements of today. The Context, Input, Process, and Product (CIPP) evaluation model was created for the decision-making towards education improvement, so this model is appropriate in this regard. However, application of this model in the actual context of medical health education is considered difficult in the education environment. Thus, in this study, literature survey of previous studies was investigated to examine the execution procedure of how the CIPP model can be actually applied. For the execution procedure utilizing the CIPP model, the criteria and indicators were determined from analysis results and material was collected after setting the material collection method. Afterwards, the collected material was analyzed for each CIPP element, and finally, the relationship of each CIPP element was analyzed for the final improvement decision-making. In this study, these steps were followed and the methods employed in previous studies were organized. Particularly, the process of determining the criteria and indicators was important and required a significant effort. Literature survey was carried out to analyze the most widely used criteria through content analysis and obtained a total of 12 criteria. Additional emphasis is necessary in the importance of the criteria selection for the actual application of the CIPP model. Also, a diverse range of information can be obtained through qualitative as well as quantitative methods. Above all, since the CIPP evaluation model execution result becomes the basis for the execution of further improved evaluations, the first attempt of performing without hesitation is essential.